Inkjet‐Printed MoS2 Transistors with Predominantly Intraflake Transport. Issue 12 (24th October 2021) - Mondal, Sandeep K.; Biswas, Ananya; Pradhan, Jyoti R.; Dasgupta, Subho
Abstract: 2D semiconductors, such as transition metal dichalcogenides (TMDs) show a rare combination of physical properties that include a large‐enough bandgap to ensure sufficient current modulation in transistors, matching electron and hole mobility for complimentary logic operation, and sufficient mechanical flexibility of the nanosheets. Moreover, the solvent‐exfoliated TMD‐nanosheets may also be processed at low temperatures and onto a wide variety of substrates. However, the poor inter‐flake transport in solution‐cast 2D‐TMD network transistors hinders the realization of high device mobility and current modulations that the intraflake transistors can regularly demonstrate. In this regard, fully printed and electrolyte‐gated, narrow‐channel MoS2 field‐effect transistors (FETs) with simultaneous high current saturation (>310 µA µm −1 ) and on–off ratio (>10 6 ) are proposed here. The transport limitation is overcome by printing an additional metal layer onto the 2D‐TMD nanosheet channel, which substantially shortens the effective channel lengths and results in predominant intraflake transport. In addition, a channel‐capacitance‐modulation induced subthermionic transport is recorded, which leads to a subthreshold slope value as low as 7.5 mV dec −1 . On the other hand, thermionic MOSFETs and fully printed depletion‐mode NMOS inverters are also presented. The demonstrated generic approach involving chemically exfoliated nanosheet inks and the absolute device yield indicates the feasibility of fully printed 2D‐TMD electronics. Abstract : Fully‐printed and electrolyte‐gated, narrow‐channel MoS2 transistors with simultaneous high‐current (>310 µA µm −1 ) and On–Off ratio (>10 6 ) are demonstrated. An additional metal layer printed onto the 2D‐transition metal dichalcogenide (TMD) nanosheet channel ensures predominant intra‐flake transport. A channel‐capacitance‐modulation induced subthermionic transport with measured subthreshold slope ≈7.5 mV dec −1 and a complete device yield indicate feasibility of fully‐printed 2D‐TMD electronics.